Colorectal endoscopic submucosal dissection (ESD). Issue 4 (August 2017) - Fuccio, Lorenzo; Ponchon, Thierry
Abstract: Endoscopic submucosal dissection (ESD) is an interventional procedure for en-bloc resection of gastrointestinal lesions. ESD is a challenging and can involve a reasonable degree of risk, therefore case selection is of crucial importance, especially in the colo-rectum. This procedure should be mainly used for dissection of lesions when there is a high suspicion of superficial malignant invasion; several classifications have been proposed in order to better identify lesions suitable for ESD. However, case selection is still an issue, since only about 8–10% of dissected lesions are superficially invading cancer and most of cases involve benign or massively invading cancer. In addition, significant differences have been reported between Asian and Western countries in regard to main outcomes, and therefore measures should be adopted as soon as possible to reduce this discrepancy.